2022
DOI: 10.3390/ijerph192315450
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Chinese Version of the Oxford Participation and Activities Questionnaire in People with Stroke

Abstract: The Oxford Participation and Activities Questionnaire was developed for generic use in the assessment of participation and activity levels. However, it is not available in Chinese and has not been tested in the stroke population. The Oxford Participation and Activities Questionnaire was translated into Chinese and culturally adapted. Its psychometric properties were examined in 100 people with stroke. The participation and activity levels of people with stroke and healthy people were also compared. Content val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The overall internal consistency α coefficient of the C-GPS-R was high at 0.944, which has also been observed in other scales translated from English to simplified Chinese [39][40][41]. In addition, the internal consistency α coefficient of the C-GCPS-R was higher than that of the Italian version (α = 0.86) [42], German version (α = 0.82) [43], and Turkish version (α = 0.903) [27].…”
Section: Plos Onesupporting
confidence: 74%
“…The overall internal consistency α coefficient of the C-GPS-R was high at 0.944, which has also been observed in other scales translated from English to simplified Chinese [39][40][41]. In addition, the internal consistency α coefficient of the C-GCPS-R was higher than that of the Italian version (α = 0.86) [42], German version (α = 0.82) [43], and Turkish version (α = 0.903) [27].…”
Section: Plos Onesupporting
confidence: 74%
“…Surprisingly, significant weak to strong correlations were demonstrated between the ArmA-C scores and TWT completion times in this study, which did not support our hypothesis. The TWT examines gait control, which involves the walking performance and cognitive function of people with stroke (30). Previous studies have suggested the important role of arm movements in maintaining coordination between the upper and lower body and gait stability during walking (9, 44) and upper-limb function was related to walking ability in people with stroke (β = 0.11, p = 0.047) (8).…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores in the Ox-PAQ-C represent greater difficulties in participation and activity. The Ox-PAQ-C has demonstrated good internal consistency (Cronbach's alpha = 0.86–0.91) and excellent test–retest reliability (ICC = 0.91–0.94) in people with chronic stroke ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation